2018
DOI: 10.21763/tjfmpc.432547
|View full text |Cite
|
Sign up to set email alerts
|

Tip 2 Diyabetli Bireylerin Sağlık Kontrol Odaklarının Değerlendirilmesi

Abstract: Introduction/Aims: The locus of control used in the management of chronic diseases is used to explain the different behaviors individuals exhibit in relation to disease This study, was done with the purpose of investigating the health locus of control and affecting factors of diabetic individuals. Methods: This study was a descriptive and cross-sectional study. Data were collected from 325 diabetic individuals living at city center. The questionnaire form and Multidimensional Health Locus of Control Scale were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…In various studies, it was observed that self-efficacy level has increased by increasing diabetes duration [16]. In our study, no significant association was found between monitoring of blood glucose and self-efficacy; however, in previous studies it was observed that self-efficacy level was higher in patients who respond positively to the question of presence or absence of regular health control [16,19]. In line with our study, in various studies no association was found between smoking and self-efficacy [15,17,18].…”
Section: Discussioncontrasting
confidence: 69%
See 4 more Smart Citations
“…In various studies, it was observed that self-efficacy level has increased by increasing diabetes duration [16]. In our study, no significant association was found between monitoring of blood glucose and self-efficacy; however, in previous studies it was observed that self-efficacy level was higher in patients who respond positively to the question of presence or absence of regular health control [16,19]. In line with our study, in various studies no association was found between smoking and self-efficacy [15,17,18].…”
Section: Discussioncontrasting
confidence: 69%
“…In our study median score increased with increasing income level but the difference wasn't statistically significant. In previous studies also a clear association wasn't observed and there are conflicting results [15,16,19,24].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations